Nutrient loading in the Vaal River over the past two decades - Ntshalintshali, Pargeant (Department of Environmental and Geographical Science, 2020)
Nutrient loading is negatively affecting South Africa’s freshwater resources and ecosystems. Anthropogenic activities are the leading causes of continuous nutrient loading in the country’s water resources. This study examines the dynamics of nutrient loading in the Vaal River. The objectives are to explore nutrient loading in the Vaal River over the past two decades and to compare the differences between the two decades. Water quality data were obtained from the Department of Water and Sanitation (DWS) Water Resource Quality Information Services (RQIS) database. Elevated nutrients of NH4+, N03, P04 3- and chlorophyll-a were observed at selected sites at various times during the 20 year period under analysis. Nutrients concentration are elevated alongside agricultural and industrial activities, and urban areas. Student t-tests investigated the difference between the two decades and in most cases showed significant differences between these decades. The last decade showed elevated nutrient levels for N03, NH4+ and chlorophyll-a in most of the DWS monitoring sites. Only P04 3- at some sites showed a reduction from the previous decade. The study concludes that upper and middle sections of Vaal River are eutrophic and hypertrophic and a trend toward a permanent state of these conditions is likely without a long-term solution to address the problem of excessive nutrient loading entering the Vaal River system.